A Multifaceted Initiative to Improve Clinician Awareness of Pain Management Disparities. (September 2014) - Bekanich, Stephen J.; Wanner, Nathan; Junkins, Scott; Mahoney, Kim; Kahn, Katherine A.; Berry, Carolyn A.; Stowell, Stephanie A.; Gardner, Allison J.
Patients belonging to some racial, ethnic, and socioeconomic groups are at risk of receiving suboptimal pain management. This study identifies health care provider attitudes, knowledge, and practices regarding the treatment of chronic pain in vulnerable patient populations and assesses whether a certified continuing medical education (CME) intervention can improve knowledge in this area. Survey responses revealed several knowledge gaps, including a lack of knowledge that the undertreatment of pain is more common in minority patients than others. Respondents identified language barriers, miscommunication, fear of medication diversion, and financial barriers as major obstacles to optimal pain management for this patient population. Participants who completed a CME-certified activity on pain management disparities demonstrated increased confidence in caring for disadvantaged patients, but only 1 of 3 knowledge items improved. Understanding clinician factors that underlie suboptimal pain management is necessary to develop effective strategies to overcome disparities and improve quality of care for patients with chronic pain.